X-Shooting ULLYSES: massive stars at low metallicity : XII. Clumped winds of O-type (super)giants in the Large Magellanic Cloud - Brands, Sarah A.; Backs, Frank; Koter, Alex de; Puls, Joachim; Crowther, Paul A.; Sana, Hugues; Tramper, Frank; Kaper, Lex; Sundqvist, Jon O.; Bestenlehner, Joachim M.; Driessen, Florian A.; Erba, Christiana; et al. (Astronomy and astrophysics, 2025)
Context: Mass loss governs the evolution of massive stars and shapes the stellar surroundings. To quantify the impact of the stellar winds, we need to know the exact mass-loss rates; however, empirical constraints on the rates are hampered by limited knowledge of their small-scale wind structure, also referred to as ‘wind clumping’. Aims: We aim to improve empirical constraints on the mass loss of massive stars by investigating the clumping properties of their winds, in particular, the relation between stellar parameters and wind structure. Methods: We analysed the optical and ultraviolet spectra of 25 O-type giants and supergiants in the Large Magellanic Cloud, using the model atmosphere code FASTWIND and a genetic algorithm. We derived the stellar and wind parameters, including detailed clumping properties, such as the amount of clumping, the density of the interclump medium, velocity-porosity of the medium, and wind turbulence. Results: We obtained stellar and wind parameters for 24 of our sample stars and found that the winds are highly clumped, with an average clumping factor of <f cl >= 33 14, an interclump density factor of <f ic> = 0.2 0.1, and moderate-to-strong velocity-porosity effects of <f vel> = 0.6 0.2. The scatter around the average values of the wind-structure parameters is large. With the exception of a significant, positive correlation between the interclump density factor and mass loss, we find no dependence of clumping parameters on the mass-loss rate or stellar properties. Conclusions: In the luminosity range we investigate here, the empirical and theoretical mass-loss rates both have a scatter of about 0.5 dex (or a factor 3). Within this uncertainty, the empirical rates and theoretical predictions are in agreement. The origin of the scatter of the empirically inferred mass-loss rates requires further investigation. It is possible that our description of wind clumping is still not sufficient to capture effects of the structured wind, which could contribute to the scatter.